ANALISIS PERAN KADER KESEHATAN DALAM ACTIVE CASE FINDING TERHADAP PENEMUAN KASUS TUBERKULOSIS ANAK - Gufron Wahyudi; Rahmawati Raharjo; Wiqodatul Ummah (Forind Press, 2026)
Pediatric tuberculosis remains a major public health concern in Indonesia, particularly due to low case detection rates and diagnostic challenges in children. One key strategy to improve pediatric TB case detection is active case finding (ACF) involving community health workers (cadres). This study aimed to analyze the role of health cadres in ACF implementation on pediatric tuberculosis case detection in Banyuwangi Regency. This study employed a quantitative cross-sectional design with a sample of 60 health cadres selected through stratified random sampling. Data were collected using structured questionnaires to assess cadre roles and secondary data from TB registers to identify pediatric TB cases. Data were analyzed using the Chi-square test with a significance level of p < 0.05. The results showed that most cadres had a good role (41.7%), and pediatric TB cases were identified in 46.7% of their working areas. Statistical analysis revealed a significant association between the role of cadres in ACF and pediatric tuberculosis case detection (p = 0.003). Cadres with better roles demonstrated higher case detection proportions. The role of community health workers in ACF significantly influences pediatric tuberculosis case detection. Strengthening cadre capacity, particularly in early detection and household contact investigation, is essential to improve pediatric TB control efforts.